Influence of Public Service Quality in Citizen Satisfaction (Study in Private Hospital Y in Padang, West Sumatra Province) - ALDRI FRINALDI; MUHAMAD ALI EMBI (Jurnal Studi Pemerintahan, 2015)
The main problem in public service particularly health care service is the public’s increasing demand for better quality of service. Therefore, hospitals as one of the means of health care providers should be  able to increase public satisfaction. This is important to win the trust of patients and/or families of patients who come for treatment. The lack of patients’ satisfaction in the quality of service in hospitals in Indonesia contributes to the Indonesians’ choice of medical treatment abroad. Therefore, the study aims to determine the influence of quality ofservices provided by the hospital toward patients’ satisfaction. This quantitative research surveyed patients in Hospital Y in Padang city using questionnaire as a research instrument. The population is all the patients and/or families of patients who are served in the hospital during the data collection in the month of May to August 2014. A sample of 100 people was selected using accidental sampling. The collected data were analyzed using frequencies, percentages and averages using SPSS  version16 for windows. Simple linear regression analysis technique was used for data analysis. Location of the study was a private hospital located in the city of Padang, West Sumatra Province, which in this research is referred as privatehospital Y. The results of this study indicates that there is a significant relation between the quality of service to the citizen satisfaction with the regression equation Y = 44.967 + 2.612 X with value of correlation (r) = 0.760, and the influence of quality of service to the public satisfaction in 57.8%. Then the results Achievement Level Respondents (TCR) in the quality of public services obtained a value of 74.8% with quite good category and to the satisfaction of the public to the TCR value of 75.3%with quite good category. It shows the quality of care in hospitals Y must be improved in order to obtain an increase in user satisfaction of the people who became his services. Based on the research findings, researchers suggest the hospital’s policy makers to prioritize the presence of doctors, particularly their punctuality during scheduled appointment as listed in the announcement board. Moreover, the patients expect the doctors to provide sufficient time to explain the diagnosis of the patients  based on their examination.KEYWORDS: Quality of Public Services, Public Satisfaction, Private Hospital